IEEE INFOCOM 2017 - IEEE Conference on Computer Communications 2017
DOI: 10.1109/infocom.2017.8057055
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and performance analysis of Wi-Fi networks coexisting with LTE-U

Abstract: In order to cope with the exponential growth of mobile traffic, mobile operators need to access more spectrum resources. LTE in unlicensed spectrum (LTE-U) has been proposed to extend the usual operation of LTE in licensed spectrum to cover also unlicensed spectrum. However, this extension poses significant challenges especially regarding the coexistence between LTE-U and legacy systems like Wi-Fi. In case of LTE-U adopts Time-Division Multiplexing (TDM) schemes to share the spectrum with Wi-Fi, we expect perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…b) Fixed duty cycle with different transmission patterns: The authors in [121], [124], [132], [133], [164] further considered different transmission patterns for LTE with fixed duty cycle, in order to either study the coexistence performance of fixed duty cycling itself, or as a baseline for other coexistence mechanisms. In general it was reported that, regardless of the transmission pattern, a fixed duty cycle for LTE could affect the Wi-Fi performance significantly.…”
Section: ) Wi-fi/lte Coexistencementioning
confidence: 99%
See 4 more Smart Citations
“…b) Fixed duty cycle with different transmission patterns: The authors in [121], [124], [132], [133], [164] further considered different transmission patterns for LTE with fixed duty cycle, in order to either study the coexistence performance of fixed duty cycling itself, or as a baseline for other coexistence mechanisms. In general it was reported that, regardless of the transmission pattern, a fixed duty cycle for LTE could affect the Wi-Fi performance significantly.…”
Section: ) Wi-fi/lte Coexistencementioning
confidence: 99%
“…In general it was reported that, regardless of the transmission pattern, a fixed duty cycle for LTE could affect the Wi-Fi performance significantly. For instance, the authors in [164] estimated the probability of collision and throughput for Wi-Fi via analytical models and ns-3 simulations, for LTE with a fixed duty cycle of 50% and different sub-frame transmission patterns. It was found that the Wi-Fi performance strongly depended on the packet size.…”
Section: ) Wi-fi/lte Coexistencementioning
confidence: 99%
See 3 more Smart Citations